Corporate Arbitration Between Contractual Autonomy and State Intervention: Reconstructing the Legal Legitimacy of Arbitral Awards - Ahmad Nizar Mohammad Syamwil; Nur Hafizah Husna; Siti Kholizah; Irpan Mauliandi Damanik; Rahmad Fauzi Hasibuan (Jurnal Cendikia ISNU SU, 2026)
The growing complexity of corporate commercial activities has intensified disputes requiring dispute resolution mechanisms capable of balancing procedural efficiency, legal certainty, and institutional legitimacy. Although arbitration has become the preferred mechanism for resolving corporate disputes because of its flexibility, confidentiality, and finality, scholarly discussions have largely examined contractual autonomy and judicial intervention as separate legal doctrines. This study aims to analyze the legal position of corporations in arbitration and reconstruct the relationship between contractual autonomy and state intervention in the enforcement of arbitral awards within the Indonesian legal system. Employing normative legal research through statutory and conceptual approaches, the study analyzes Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution, relevant legal doctrines, and scholarly literature using systematic legal interpretation and prescriptive legal reasoning. The findings demonstrate that corporations, as independent legal subjects, possess full legal capacity to submit disputes to arbitration and are legally bound by arbitral awards arising from their contractual consent. At the same time, judicial authority is confined to limited procedural supervision concerning the recognition, enforcement, and annulment of arbitral awards without extending to substantive review. This study argues that the legitimacy of corporate arbitration is sustained through the complementary interaction between private contractual autonomy and limited state intervention, rather than through the predominance of either principle alone. Accordingly, the article contributes to contemporary arbitration scholarship by offering an integrated conceptual framework that reinforces legal certainty, procedural fairness, and corporate confidence while preserving the finality of arbitral awards.